Vigas em concreto armado reforçadas com EBR-CFRP submetidas a degradação por temperatura e umidade em condição acelerada - Morgan, Gabriel Henrique (2021)
The need to strengthen concrete beams to increase the load capacity due to change not foreseen in the initial project or to problems related to the degradation of this structural system makes the use of composites in Fiber Reinforced Polymer (FRP) a viable alternative for the execution of strengthening systems. However, due to the environment in which FRPs are inserted, their durability can also be affected over time. In this context, the present research aims to evaluate the degradation in the accelerated condition of reinforced concrete beams with and without using the strengthening system with carbon fiber sheets when immersed in constant humidity and controlled temperature. For this, eight reinforced concrete beams were made, with dimensions 12cm x 20cm x 250cm, longitudinal reinforcement rate equal to 0.75%, and concrete with compressive strength of 30MPa. The set of eight beams were divided into two groups according to the exposure environment; four were kept in natural environmental conditions, and four were exposed to the accelerated degradation protocol. In addition, each group had two pairs of beams with and without the application of CFRP strengthening. As a result, there was a significant increase in the load capacity for beams strengthened with CFRP compared to not strengthened, with an average increase of 41.5%. Regarding the influence of the environments, after the exposure period, the beams without the CFRP strengthening system showed similarity both in behavior and in the mode of ruin. However, the strengthened beams showed changes in the failure mode, changing the ductility of the models. To analyze the average bonding stress between the concrete and the strengthening system, pullout tests were executed, showing a reduction of 35.7% compared to the reference model. Finally, the analyzes were performed based on normative recommendations, comparing their maximum load and strain results with those obtained in experimental tests. Therefore, according to the ductility analysis, material deformation, cracking, and failure mode, there was evidence that the humid environment with controlled temperature may have caused degradation in the connection between the strengthening system and the concrete substrate.